Obesity, dyslipidemia and brain age in first-episode psychosis. (April 2018) - Kolenic, Marian; Franke, Katja; Hlinka, Jaroslav; Matejka, Martin; Capkova, Jana; Pausova, Zdenka; Uher, Rudolf; Alda, Martin; Spaniel, Filip; Hajek, Tomas
Abstract: Introduction: Obesity and dyslipidemia may negatively affect brain health and are frequent medical comorbidities of schizophrenia and related disorders. Despite the high burden of metabolic disorders, little is known about their effects on brain structure in psychosis. We investigated, whether obesity or dyslipidemia contributed to brain alterations in first-episode psychosis (FEP). Methods: 120 participants with FEP, who were undergoing their first psychiatric hospitalization, had <24 months of untreated psychosis and were 18–35 years old and 114 controls within the same age range participated in the study. We acquired 3T brain structural MRI, fasting lipids and body mass index. We used machine learning trained on an independent sample of 504 controls to estimate the individual brain age of study participants and calculated the BrainAGE score by subtracting the chronological from the estimated brain age. Results: In a multiple regression model, the diagnosis of FEP (B = 1.15, SE B = 0.31, p < 0.001) and obesity/overweight (B = 0.92, SE B = 0.35, p = 0.008) were each additively associated with BrainAGE scores (R 2 = 0.22, F(3, 230) = 21.92, p < 0.001). BrainAGE scores were highest in participants with FEP and obesity/overweight (3.83 years, 95%CI = 2.35-5.31) and lowest in normal weight controls (−0.27 years, 95%CI = −1.22-0.69). LDL-cholesterol, HDL-cholesterol or triglycerides were not associated with BrainAGE scores. Conclusions: Overweight/obesity may be an independent risk factor for diffuse brain alterations manifesting as advanced brain age already early in the course of psychosis. These findings raise the possibility that targeting metabolic health and intervening already at the level of overweight/obesity could slow brain ageing in FEP. Highlights: Both overweight/obesity and FEP were associated with advanced brain age. The effects of overweight/obesity on brain age were additive to the effects of FEP. Brain versus chronological age difference was largest in FEP with overweight/obesity. Advanced brain age in FEP and overweight/obesity was not related to treatment with antipsychotics.